2003
DOI: 10.1016/s1050-4648(02)00160-2
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Crassostrea gigas hemocyte oxidative metabolism by flow cytometry and the inhibiting capacity of pathogenic vibrios

Abstract: A flow cytometric method to measure the production of oxidative metabolism products was adapted for use with Crassostrea gigas hemocytes. The method is based upon the oxidation, by hydrogen peroxide (H2O2), of intracellular 2',7'-dichlorofluorescin (DCFH) to green-fluorescent dichlorofluorescein. Activation of the respiratory burst (RB) was tested using phorbol myristate acetate with no success. By contrast, activation by zymosan particles increased oxidation of DCFH in C. gigas hemocytes, mainly granulocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
1
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 175 publications
(109 citation statements)
references
References 31 publications
(42 reference statements)
8
97
1
3
Order By: Relevance
“…This implies another origin of ROS production, for example, a possible increase of ROS associated with the immune response. In bivalves, ROS production during infection have been suggested to be a host defense mechanism to counter attacks of pathogenic bacteria (Canesi et al 2002;Lambert et al 2003;Labreuche et al 2006b;Wang et al 2010). The increase of CAT, GPX and SOD protein-specific activity shows that moribund larvae increased the proportion of antioxidant enzymes in their tissues, thus pinpointing the importance of antioxidant defenses during the massive mortality event.…”
Section: Characterization Of the Massive Mortalitymentioning
confidence: 99%
“…This implies another origin of ROS production, for example, a possible increase of ROS associated with the immune response. In bivalves, ROS production during infection have been suggested to be a host defense mechanism to counter attacks of pathogenic bacteria (Canesi et al 2002;Lambert et al 2003;Labreuche et al 2006b;Wang et al 2010). The increase of CAT, GPX and SOD protein-specific activity shows that moribund larvae increased the proportion of antioxidant enzymes in their tissues, thus pinpointing the importance of antioxidant defenses during the massive mortality event.…”
Section: Characterization Of the Massive Mortalitymentioning
confidence: 99%
“…These anticoagulants chelate calcium ions, which are involved in haemocyte immune function [52]. This alters the rate of phagocytosis and production of reactive oxygen species in the bivalves Mytilus galloprovincialis [51] and Crassostrea gigas [53] and the level of prophenoloxidase activity in the cockroach Blaberus craniifer [54]. Though the anticoagulant affects the haemocyte function, stress studies in bivalve molluscs using anticoagulants have shown statistically significant differences between treated and controlled groups, suggesting that anticoagulants do not invalidate the studies using them [53].…”
Section: In Vitro Assessment Of Haemocytesmentioning
confidence: 99%
“…Cheng et al [6][7][8][9][10] also used the nitroblue tetrazolium assay. Lambert et al [53] developed an alternative procedure for measuring respiratory burst in oyster haemocytes using flow cytometry. This paper highlights the importance of initiating the oxidative burst process prior to analysis using suitable activating reagents.…”
Section: Respiratory Burstmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemocytes act as cellular immune eVectors through their capacities to phagocytize, encapsulate, and subsequently degrade invading foreign materials (Montes et al 1995;Chu 2000;Canesi et al 2002). Hemocytes express various hydrolytic enzymes and are able to produce reactive oxygen species (ROS), both of which are involved in the destruction of ingested or encapsulating nonself materials (Adema et al 1991;Toreilles et al 1996;López et al 1997;Cima et al 2000;Bayne et al 2001;Lambert et al 2003;Terahara and Takahashi 2008). Hemocytes are also involved in other vital functions of bivalve biology and physiology, including nutrient transport and digestion, shell and tissue formation, and repair, as well as homeostatic maintenance (Cheng 1996(Cheng , 2000Chu 2000;Beninger et al 2003;Mount et al 2004).…”
Section: Introductionmentioning
confidence: 99%